Incommensurate and Collinear Phases in a Doped Quantum Anti-ferromagnet - Barford, W; Jadhav, S (1994)
The Schwinger Boson mean field theories of the `t-J' model are extended by the consideration of anisotropic order parameters. This has two effects. First, a collinear phase, in which the spins are anti-ferromagnetically aligned in one direction and ferromagnetically aligned in the other, is found to be stable over a significant range of the phase diagram. Second, the (1,1) and (1,0) spiral phases become very close in energy. The inclusion of weak intra-sublattice coupling may therefore stabilise the (1,0) spiral with respect to the (1,1) spiral, thus harmonising theory and experiment.